Factors That Affect the Sensitivity of Imaging Modalities in Primary Hyperparathyroidism. (20th February 2021) - Zhu, Minting; He, Yang; Liu, Tingting; Tao, Bei; Zhan, Weiwei; Zhang, Yifan; Xie, Jing; Chen, Xi; Zhao, Hongyan; Sun, Lihao; Liu, Jianmin
Abstract : Background . Cervical ultrasound, 99m Tc-sestamibi single-photon emission computed tomography/computed tomography ( 99m Tc-MIBI SPECT/CT), and cervical CT are routinely used in preoperative localization of primary hyperparathyroidism (PHPT). However, false-negative imaging results are also frequently encountered in clinical practice. Exploring the factors that affect the sensitivity of these imaging modalities is important for the surgical management of PHPT patients. Methods . Clinical data of 352 PHPT patients hospitalized in our center from January 2011 to December 2015 were retrospectively collected to evaluate the sensitivity of 3 imaging modalities in the preoperative localization of parathyroid lesions. The ROC curve analysis was used to explore the clinical factors affecting the sensitivity of localization, and the cut-point(s) of related factors were determined. Results . 99m Tc-MIBI SPECT/CT has the highest sensitivity among the localization modalities commonly used, reaching 91.1% (86.0%–94.8%). When the lengths of parathyroid lesions were ≤1.3 cm, the sensitivity of neck ultrasonography significantly decreased, while the sensitivity of 99m Tc-MIBI SPECT/CT decreased with parathyroid lesions ≤1.3 cm or serum PTH≤252 pg/ml. 99m Tc-MIBI SPECT/CT was less effective in localizing the hyperplasia lesions. Neck ultrasonography combined with 99m Tc-MIBI SPECT/CT can effectively improve the accuracy of preoperative localization of parathyroid lesions to 96.2% (92.7%–98.1%). Conclusions . Small parathyroid lesion and mild elevation of serum PTH would reduce the accuracy of parathyroid localization in PHPT patients.